Hydrogen Evolution Reaction: Cobalt Based Nanoparticles Embedded Reduced Graphene Oxide Aerogel for Hydrogen Evolution Electrocatalyst (Part. Part. Syst. Charact. 7/2019). (19th July 2019) - Koo, Sung Hwan; Li, Dong Jun; Yun, Taeyeong; Choi, Dong Sung; Lee, Kyung Eun; Lee, Gil Yong; Oh, Youngtak; Lim, Joonwon; Padmajan Sasikala, Suchithra; Lee, Ho Jin; Kim, In Ho; Jung, Hong Ju; et al.
Abstract : By freeze‐drying and heat treatment, various cobalt based nanoparticles decorated reduced graphene oxide could be obtained with small, uniform nanoparticle distribution. In article number1900090, Sang Ouk Kim and co‐workers suggest a simple route toward ultrasmall, uniform nanoparticles decorated graphene surfaces with maximal surface area and efficient charger transfer.